FREQUENCY OF HYPOMAGNESEMIA IN PATIENTS WITH UNCONTROLLED TYPE II DIABETES MELLITUS: Hypomagnesemia in Type 2 Diabetes Mellitus - Siddiqui, Muhammad Umer; Ali, Imtiaz; Zakariya, Manzar; Asghar, Syed Parvez; Ahmed, Muhammad Rashid; Ibrahim, Ghulam Hussain (Pakistan Armed Forces Medical Journal, 2016)
Objective: The objective of this study was to determine the frequency of Hypomagnesemia in patients with uncontrolled type II diabetes mellitus.Study Design: Cross-sectional study.Place and Duration of Study: Department of Medicine, PNS Shifa Naval Hospital Karachi, from Jul 2012 to Dec 2012 over a period of six months.Material and Methods: In this study, three hundred and twenty three patients of uncontrolled diabetes mellitus type-II on oral hypoglycemic agents for more than five years, presenting to medical OPD, were recruited. All patients fulfilled inclusion and exclusion criteria. Blood samples of all patients for serum HbA1c and serum magnesium levels were analyzed at the time of enrollment. Statistical analysis was done on SPSS 20.Results: Out of 323 patients, 243 (75.23%) were males and 80 (24.76%) were females with the age ranging from 40 – 65 years (mean age and SD 54.76 ± 6.43). Hypomagnesemia was found in 117 patients, without any significant difference in men and women (38.45% and 35.39% respectively). The mean duration of diabetes was 12.5 years (ranging from 5 to 22 years). By frequency test in SPSS-20, the highest frequency of hypomagnesemia (49.42%) is seen in (8.6–9.0) HbA1c group while lowest frequency hypomagnesemia (15.38%) is seen in (>10.0) HbA1c level group mean standard deviation and p-value calculated by Pearson correlation statistic in SPSS-20 for quantitative variables (HbA1c, Magnesium level).Conclusion: Hypomagnesemia is frequent in poorly controlled type-II diabetes mellitus having increased level of HbA1c. So it may be prudent in clinical practice to periodically monitor plasma magnesium and HbA1c in type-II diabetes mellitus patients.